Women's likelihood of holding a senior management position is considerably lower than men's - especially in the financial sector - Elke Holst; Martin Friedrich (DIW Economic Bulletin, 2016)
Women remain grossly underrepresented in management positions in Germany. However, what has been dubbed the gender leadership gap, i.e., the difference between the share of all employees who are women and the share of women in senior management positions, varies considerably across different industries. The present report shows that the largest gender gap in the likelihood of holding a senior management position is to be found in the financial sector. Possible explanations include an exceptionally masculine culture and the specific legal requirements of CEOs in the financial sector that are implicitly biased toward men. Furthermore part-time work generally has an adverse effect on women's career prospects: for many management positions, being able to work full-time is a prerequisite that often excludes women from taking on these positions due to the traditional division of household and family labor. Policy-makers and the business community should therefore adopt measures to increase gender equality when it comes to working hours. The 'family working-time benefits model' and improvements in the quality of child day care proposed by DIW Berlin would be steps in the right direction.
Keywords: G2; J16; J78; L32; M14; M51; 330; gender; gender leadership gap; managerial positions; promotion probability; Executive Committees (ExCos); glass ceiling; working hours; motherhood penalty; financial sector; BaFin; corporate culture; temporal flexibility